2018
DOI: 10.1186/s41983-018-0016-0
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia among non-depressed multiple sclerosis patients: a cross-sectional study

Abstract: BackgroundInsomnia is a common problem that affects approximately 50% of patients with multiple sclerosis (MS), who suffer from sleep disturbances. In general, persons with insomnia are at a higher risk of developing depression. This study was conducted to assess insomnia among non-depressed MS patients in Saudi Arabia.MethodsBased on the Patient Health Questionnaire-9 (PHQ-9), those who scored 4 or less for depression out of 598 MS patients were selected (n = 112). A cross-sectional study was conducted to int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
1
13
1
Order By: Relevance
“…Our findings show significant difference of education level concerning its possible influence on sleep quality in patients with RRMS. This result is consistent with data of Alhazzani A.A. et al that the level of education is considered as a risk factor for development of insomnia on a condition of absence of depression [23]. We found no valuable difference between both groups concerning gender, that does not match with previously reported results that SD in MS patients are prevalently associated with female gender [9].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings show significant difference of education level concerning its possible influence on sleep quality in patients with RRMS. This result is consistent with data of Alhazzani A.A. et al that the level of education is considered as a risk factor for development of insomnia on a condition of absence of depression [23]. We found no valuable difference between both groups concerning gender, that does not match with previously reported results that SD in MS patients are prevalently associated with female gender [9].…”
Section: Discussionsupporting
confidence: 91%
“…As regard to marital status, around two third were single, this finding was in contrast with [24] who mentioned that more than half of respondents (55.4%) were married.…”
Section: Discussioncontrasting
confidence: 58%
“…Regarding diagnosed years with MS, two third of MS patients had a diagnosed durations from one up to five years, this in line with [21] who emphasized that the mean time interval between the first symptoms and disease diagnosis was around two years. While, [24] reported that the mean duration of the disease was around five years.…”
Section: Discussionmentioning
confidence: 99%
“…In addition other articles related to Health and Sleep Physiology were included to support our general arguments. Articles were reviewed by two independent reviewers and a total of 37 articles were selected for inclusion in the present review [4,14,16,17,18,19,22,23,24,25,26,29,31,32,33,34,35,36,37,38,39,41,42,43,49,50,51,53,55,56,61,62,63,64,66,67,70].…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study it was reported that 42% of MS patients had difficulty in initiating sleep, 53% reported extended awakenings, and 58% reported staying awake for the rest of the time [38]. In general, persons with insomnia are at a higher risk of developing depression while the prevalence of insomnia in non-depressed MS patients is much lower compared to all MS patients (12.5%) [39].…”
Section: Insomniamentioning
confidence: 99%